Application of Antioxidant Compounds in Bone Defect Repair - Jiajia Wang; Yubing Zhang; Qingming Tang; Yinan Zhang; Ying Yin; Lili Chen (MDPI AG, 2024)
Bone defects caused by trauma, tumor resection, and infections are significant clinical challenges. Excessive reactive oxygen species (ROS) usually accumulate in the defect area, which may impair the function of cells involved in bone formation, posing a serious challenge for bone repair. Due to the potent ROS scavenging ability, as well as potential anti-inflammatory and immunomodulatory activities, antioxidants play an indispensable role in the maintenance and protection of bone health and have gained increasing attention in recent years. This narrative review aims to give an overview of the main research directions on the application of antioxidant compounds in bone defect repair over the past decade. In addition, the positive effects of various antioxidants and their biomaterial delivery systems in bone repair are summarized to provide new insights for exploring antioxidant-based strategies for bone defect repair.